The influence of power stator windings of the asynchronous traction motors for dynamic workload elements of traction drive locomotive - Bondarev, O. M. (Science and Transport Progress, 2010)
The results of studies on determination of loading level of tractive drive elements in some operating conditions, when the values of frequencies of the change of feeding currents of stator windings are to be obtained in both subcritical and ultracritical zones for two types of the tractive gear are presented in the paper.